Non-coding RNAs: Key players in T cell exhaustion - Li, Kun; Wang, Ziqiang (Frontiers in Immunology, 2022)
T cell exhaustion caused by continuous antigen stimulation in chronic viral infections and the tumor microenvironment is a major barrier to successful elimination of viruses and tumor cells. Although immune checkpoint inhibitors are expected to reverse T cell exhaustion, shortcomings, such as off-target effects and single targets, limit their application. Therefore, it is important to identify molecular targets in effector T cells that can simultaneously regulate the expression of multiple immune checkpoints. Over the past few years, non-coding RNAs, including microRNAs and long non-coding RNAs, have been shown to participate in the immune response against viral infections and tumors. In this review, we focus on the roles and underlying mechanisms of microRNAs and long non-coding RNAs in the regulation of T cell exhaustion during chronic viral infections and tumorigenesis. We hope that this review will stimulate research to supply more precise and effective immunotherapies for viral infections and tumors.